2019
DOI: 10.1182/blood-2019-131708
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Correction of ELANE mutations in Primary HSPCs of Severe Congenital Neutropenia Patients Using CRISPR/Cas9 and rAVV6 HDR Repair Templates

Abstract: Patients with the rare pre-leukemia bone marrow failure syndrome severe congenital neutropenia (CN) have reduced numbers of neutrophils in peripheral blood (<500/µl) leading to frequent infections and requiring chronic granulocyte stimulating factor (G-CSF) treatment. The majority of patients harbor heterogenous mutations in ELANE, coding for Neutrophil Elastase. Up to now, the only curative therapy for CN patients that do not respond to G-CSF or with overt AML remains hematopoietic stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Using CRISPR/Cas 9 to edit these mutations and adeno-associated virus 6 (rAAV6) to deliver the template for repair the structure by homology directed repair (HDR), they successfully achieved an increasing number of mature neutrophils with NET formation and chemotaxis improved. At the same time, there were no changes in functionality of the produced cells (108). In 2020, another team supervised by Skokowa successfully restored neutrophil "maturation arrest" in SCN cells by complete knockout of the ELANE gene (ELANE KO).…”
Section: Crispr/cas9 Gene Editingmentioning
confidence: 99%
“…Using CRISPR/Cas 9 to edit these mutations and adeno-associated virus 6 (rAAV6) to deliver the template for repair the structure by homology directed repair (HDR), they successfully achieved an increasing number of mature neutrophils with NET formation and chemotaxis improved. At the same time, there were no changes in functionality of the produced cells (108). In 2020, another team supervised by Skokowa successfully restored neutrophil "maturation arrest" in SCN cells by complete knockout of the ELANE gene (ELANE KO).…”
Section: Crispr/cas9 Gene Editingmentioning
confidence: 99%
“…Investigative ther a pies include nic o tin amide to increase the expres sion of G-CSF and G-CSF recep tors in SCN, 67,68 neu tro phil elas tase inhib i tors to pre vent the unfolded pro tein response from mutated ELANE, 69,70 and gene editing to repair mutated ELANE or reduce trans la tion of the ELANE gene. [71][72][73] Nicotinamide has been used in a small clin i cal trial with pos i tive results, but other modal i ties have only reported results in the pre clin i cal set ting. The use of smallmol e cule inhib i tors to pro mote non sense sup pres sion in patients with ter mi na tion SBDS muta tions (c.183-184TA > TC) has also dem on strated prom ise in reduc ing apo pto sis and increas ing neu tro phil mat u ra tion in bone mar row pro gen itor cells.…”
Section: Gene Ther Apy and Other Poten Tial Treat Ment Modal I Ties For Con Gen I Tal Neutropeniamentioning
confidence: 99%